2000
DOI: 10.1007/bf03343757
|View full text |Cite
|
Sign up to set email alerts
|

Extremely high levels of estradiol and testosterone in a case of polycystic ovarian syndrome. Hormone and clinical similarities with the phenotype of the α estrogen receptor null mice

Abstract: A 19-year-old nulliparous hirsute woman was evaluated for the very high serum levels of testosterone (T) and estradiol (E2) measured in an outside laboratory. Menarche had occurred at 11 years and was followed by regular menses. We confirmed the high levels of T (9-16 ng/ml, nv 0.2-0.8) and E2 (>1,000 pg/ml, nv 30-120). LH and FSH were consistently high (73-118 mU/l and 18-29 mU/l, respectively; LH/FSH ratio=4.1-4.7) and responsive to iv GnRH (LH baseline=118 mU/I, 30 min=290; FSH baseline=25 mU/l, 30 min=46).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
2
3
0
Order By: Relevance
“…There was significant increase (p < 0.05) in the testosterone concentration of PCOS group when compared with Non-PCOS control group (Table 1). This study is in agreement with the work of Bartolone et al (2000) who reported an extremely high level of Testosterone in PCOS [19]. This emphasizes the importance of testosterone in diagnosing of PCOS.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…There was significant increase (p < 0.05) in the testosterone concentration of PCOS group when compared with Non-PCOS control group (Table 1). This study is in agreement with the work of Bartolone et al (2000) who reported an extremely high level of Testosterone in PCOS [19]. This emphasizes the importance of testosterone in diagnosing of PCOS.…”
Section: Discussionsupporting
confidence: 93%
“…The concentration of Estradiol in PCOS subjects in this study increased significantly in comparison with the control subject (Table 1). This correlates with the research work of Bartolone et al who reported an extremely high level of Estradiol in PCOS, and suggested that the differential diagnosis of high levels of E2 +/− Testosterone should include PCOS [19].…”
Section: Discussionsupporting
confidence: 90%
“…Anovulation is associated with low estradiol secretion, mainly due to peripheral extraglandular conversion and minimal progesterone production [48]. Hashemi et al found decreased estradiol levels in PCOS, while studies point out to exceedingly high estradiol levels [49], [50]. The increase in the level of bioavailable estradiol in PCOS can be attributed to reduced sex hormone-related globulin levels [51], which are also associated with obesity and testosterone levels [38].…”
Section: Discussionmentioning
confidence: 99%
“…Serum concentrations of E1 and estradiol (E2) are higher in women with PCOS than controls, but the ranges overlap widely (15,16). It has also been suggested that impaired FSH release by chronic acyclic estrogen production derived from nonglandular aromatization of circulating androgens could be responsible for anovulation in PCOS (14).…”
mentioning
confidence: 97%